DCOM distributed computing model for terrain visualization - Wan Zahari, Wan Nur Ilyana (Penerbit UTM, 2007)
Terrain visualization is an important application of numerous fields such as civil engineering, urban planning, military, virtual reality and Geographic Information System (GIS) The input to the terrain visualization problem is usually a large terrain model, consisting of elevation data sampled and corresponding aerial and/or satellite texture data, which is mapped onto the reconstructed terrain surface. The output is rendered images of the terrain surface. The advent of the distributed technology suggests the running of this type of application over the network, in a client/server scenario. This technology simplifies access to terrain data and can be used to spread information/data to a multitude of users. However, terrain data consists of very large data size while the bandwidth is limited. Therefore, there is a need to enable the terrain visualization performance in a distributed environment with reasonable response time and bandwidth